Several local food plants with the potential as hosts for Spodoptera frugiperda (Lepidoptera: Noctuidae) - Novri Nelly; Hasmiandy Hamid; Eka Candra Lina; Yunisman Yunisman; Hidrayani Hidrayani; Dwi Monica Widya Sari (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nelly N, Hamid H, Lina EC, Yunisman, Hidrayani, Widyasari DM. 2022. Several local food plants with the potential as hosts for Spodoptera frugiperda (Lepidoptera: Noctuidae). Biodiversitas 23: 1693-1699. Fall armyworm (Spodoptera frugiperda) or abbreviated as FAW is a major invasive pest of corn crops in America, its native country. Therefore, this study aims to examine the effect of several plant types as hosts on FAW biology and reproduction. It was conducted at the Insect Bioecology Laboratory, Department of Plant Protection, Andalas University using a completely randomized design (CRD) with 3 treatments and 4 replications. The FAW larvae from the field were fed with different plant leaves, namely corn (Zea mays), rice (Oryza sativa), soybeans (Glycine max), and reared until the second generation. Meanwhile, the larvae in the second generation were used as test insects with different feed treatments. Observations were made on the morphology and life parameters of FAW, including the length of the stadia, egg, larvae, pupae, and adult, as well as the laying time and pattern, with the number of eggs produced. The results showed that there were no morphological differences in S. frugiperda, except for the size. Moreover, the body size of the adult-derived from larvae fed with soybean leaves, namely 25.95 mm, was the smallest compared to corn and rice, while the shortest time for larvae development from instar I to VI was obtained with corn leaf feed for 13.55 days. The life span of females derived from larvae fed on soybean leaves was shorter than the others. Larvae fed on soybeans, female life span was 26.00, rice was 34.00 and corn was 31.44 days. Adult females of larvae given soybean leaves produced the highest number of eggs (879.44 eggs) compared to rice (505.00 eggs) and maize (546.33 eggs). Local food crops other than corn, namely rice and soybeans, can be potential hosts for S. frugiperda.